Navigating Dual Roles: Work-Family Balance Strategies among Married Working Women in Kageshwori Manohara, Nepal - Chauhan, Nar Kumar (Chhahari छहारी, 2026)
This study examines the dual responsibilities of married working women, focusing on their family and professional responsibilities in Ward No. 9 of Kageshwori Manohara Municipality in Kathmandu, Nepal. Adopting a quantitative descriptive design, the study employed purposive sampling to collect data from 80 married working women aged between 25- 45 years using a semi-structured survey questionnaire. The study explored the types and nature of women’s responsibilities, challenges they faced, and strategies they adopted for maintaining work-family balance. Findings indicate that women continue to shoulder a disproportionate share of family responsibilities, particularly in caregiving and household management. Time constraints, limited family support, rigid workplace structures, societal expectations, and persistent gender norms significantly contribute to work-family conflict. To manage these challenges, respondents reported strategies such as flexible work arrangements, task prioritization, mentorship from female role models, and technology utilization. The study stresses the need for shared household responsibilities and gender-responsive workplace policies to promote work-family balance and advance gender equality, offering implications for both organizations and policymakers.